2018
DOI: 10.3389/fnbeh.2018.00089
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Psychosocial Predictors of Aggression: Variable Selection and Model Building With Component-Wise Gradient Boosting

Abstract: Rationale: Given datasets with a large or diverse set of predictors of aggression, machine learning (ML) provides efficient tools for identifying the most salient variables and building a parsimonious statistical model. ML techniques permit efficient exploration of data, have not been widely used in aggression research, and may have utility for those seeking prediction of aggressive behavior.Objectives: The present study examined predictors of aggression and constructed an optimized model using ML techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Of the studies included in the systematic review, six assessed predictors of criminal recidivism [20][21][22][23][24][25], two assessed predictors of the type of criminal offence [26,27], three assessed predictors of physical violence during inpatient stay [28][29][30], and six assessed predictors of violent offending and aggression following discharge [24,[31][32][33][34][35][36][37][38]. All studies, apart from two [21,30], used clinical input features, including socio-demographic information, questionnaires, and psychometric measures to derive predictions.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies included in the systematic review, six assessed predictors of criminal recidivism [20][21][22][23][24][25], two assessed predictors of the type of criminal offence [26,27], three assessed predictors of physical violence during inpatient stay [28][29][30], and six assessed predictors of violent offending and aggression following discharge [24,[31][32][33][34][35][36][37][38]. All studies, apart from two [21,30], used clinical input features, including socio-demographic information, questionnaires, and psychometric measures to derive predictions.…”
Section: Resultsmentioning
confidence: 99%
“…The research team used a two-stage applied machine learning approach for variable selection and model building to predict first drink of the day. This approach has demonstrated effective performance in prior research ( Bauer et al, 2019 ; R. Suchting, Gowin, Green, Walss-Bass, & Lane, 2018 ; Suchting, Hébert, Ma, Kendzor, & Businelle, 2019 ; Walss-Bass, Suchting, Olvera, & Williamson, 2018 ). We used successive passes through two algorithms (component-wise gradient boosting and backward elimination) to reduce a set of random and daily EMA predictors of imminent drinking.…”
Section: Methodsmentioning
confidence: 99%
“…The number of algorithm iterations is determined using 10-fold cross-validation, with two consequences: (1) optimized predictive performance via limited overfitting and (2), an inherent variable selection capacity, as only so many predictors may be chosen in the finite set of iterations before the algorithm terminates. Recent research has demonstrated the utility of the CGB algorithm for deriving optimized, parsimonious models of outcomes in health and behavioral sciences; examples include determinations of the best (a) inflammatory predictors of adolescent depression and anxiety [ 54 ], (b) psychosocial and genetic predictors of aggression [ 55 ] and (c) cognitive test predictors of pediatric bipolar disorder [ 56 ].…”
Section: Methodsmentioning
confidence: 99%